Femoral neck cortical bone distribution of dryopithecin apes and the evolution of hominid locomotion. Issue 136 (November 2019) - Pina, Marta; Alba, David M.; Moyà-Solà, Salvador; Almécija, Sergio
Abstract: Only a few postcranial remains have been assigned to the Miocene great ape Dryopithecus fontani, leading to uncertainties in the reconstruction of its overall body plan and positional behavior. Here we shed light on the locomotor repertoire of this species through the study of the femoral neck cortical bone (FNCB) distribution of IPS41724, a partial proximal femur from the Abocador de Can Mata locality ACM/C3-Az (11.9 Ma, middle Miocene; Vallès-Penedès Basin, Spain) attributed to this taxon. This specimen was scanned through computed tomography to measure the superior (SUP) and inferior (INF) cortical thicknesses at the middle and the base of the femoral neck. Measurements were compared with a sample of extant primates and the femur IPS18800.29 from the younger great ape Hispanopithecus laietanus from Can Llobateres 2 (9.6 Ma, late Miocene; Vallès-Penedès Basin), previously shown to display a homogeneous FNCB distribution at the midneck section coupled with postcranial adaptations to below-branch suspensory behaviors. Our analyses indicate an asymmetric FNCB distribution for IPS41724 (SUP/INF index = ∼0.4 at the midneck and base of the neck sections), comparable with that of quadrupedal primates and bipedal hominins (including early australopiths), but contrasting with the homogeneous FNCB distribution of Hispanopithecus and extant great apes. An asymmetrical FNCB distribution has been associated with stereotyped loads at the hip joint (as in both quadrupedal and bipedal taxa). Our results therefore support a significant quadrupedal component of the positional behavior of Dryopithecus, thus strengthening the argument that plesiomorphic generalized quadrupedalism was still a major locomotor behavior for Miocene great apes. If that were the case, it could have deep implications for the origins of hominin bipedalism.